Effectiveness and safety of tenofovir amibufenamide and its comparison with tenofovir alafenamide in patients with chronic hepatitis B: results from a retrospective real-world study - Li, Lanqing; Zhou, Jing; Li, Yujing; Wang, Fada; Zhang, Dongmei; Wang, Menglan; Tao, Yachao; Chen, Enqiang (Frontiers in Pharmacology, 2023)
Background/Aim: Tenofovir amibufenamide(TMF) has potent antiviral efficacy in randomized clinical study. This study aimed to reveal the effectiveness and safety of TMF in real-world, and compared TMF to tenofovir alafedimide (TAF) in patients with chronic hepatitis B(CHB). Methods: This was a retrospective study. TMF-treated CHB patients were divided into treatment-naive(TN) group and treatment-experienced(TE) group. And TAF-treated patients were enrolled using propensity score matching method(PSM). We assessed the virological response(VR, HBV DNA<100IU/mL) rates, renal function and blood lipids changes during 24 weeks of treatment. Results: The VR rates at week 24 were 93%(50/54) in TN group and 95%(61/64) in TE group. The ratios of alanine transaminase (ALT) normalization was 89%(25/28) in TN group and 71%(10/14) in TE group(p=0.306).Additionally, no matter in TN group or TE group, serum creatine decreased[-4.44±13.55umol/L vs -4.14±9.33umol/L, p=0.886], estimated glomerular filtration rate (eGFR) increased[7.01±12.49ml/min/1.73m2 vs 5.50±8.16ml/min/1.73m2, p=0.430], and low-density lipoprotein cholesterol(LDL-C) levels increased[0.09±0.71mmol/L vs 0.27±0.68mmol/L, p=0.152], but total cholesterol/high-density lipoprotein cholesterol (TC/HDL-C) values decreased continuously from 3.26±1.05 to 2.49±0.72 in TN group and from 3.31±0.99 to 2.88±0.77 in TE group. After PSM, we further compared VR rates between TMF and TAF cohorts. The VR rates among TN patients was higher in TMF cohort[92%(35/38) vs. 74%(28/38), (p=0.033)]. The VR rates among TE patients showed no statistical difference between TMF and TAF cohorts. Conclusion: TMF had profound antiviral effectiveness and no adverse effects on renal function and blood lipid. Additionally, TMF was more efficient than TAF in inhibiting viral replication.